Dyskryminacja dzieci pozamałżeńskich w ustawodawstwie cywilnym w Drugiej Rzeczypospolitej i próby jej przezwyciężenia w projektach kodyfikacyjnych - Leonard Górnicki (Prawo)
The article points out that of the five coexisting systems of family law in independent Poland that originated in the partition era, which were treated as Polish district law (namely: the French-Polish legislation in the central lands, the Russian legislation in the eastern lands, the Austrian legislation in the southern lands, the provisions of the Austrian legislation in force together, as well as some Austrian marriage laws and the Hungarian Personal Marriage Law of 1894 in Spiš and Orava, and finally German legislation in the western lands of the Second Republic of Poland)— all discriminated against extramarital children, then known as “non-marital” and “illegitimate” or “natural” children. The rule, therefore, was that there existed a difference in the legal position of marital and extramarital children.